Myeloid-Specific Expression of Ron Receptor Kinase Promotes Prostate Tumor Growth - Gurusamy, Devikala (2013)
Ron receptor kinase (MST1R) is important in promoting epithelial tumorigenesis, but the potential contributions of its specific expression in stromal cells have not been examined. Herein, we show that the Ron receptor is expressed in mouse and human stromal cells of the prostate tumor microenvironment. To test the significance of stromal Ron expression, prostate cancer cells were orthotopically implanted into the prostates of either wild type (WT) or Ron tyrosine kinase deficient (TK−/−; Mst1r−/−) hosts. In TK−/− hosts, prostate cancer cell growth was significantly reduced compared to tumor growth in TK+/+ hosts. Prostate tumors in TK−/− hosts exhibited an increase in tumor cell apoptosis, macrophage infiltration and altered cytokine expression. Reciprocal bone marrow transplantation studies and utilizing myeloid cell specific ablation of Ron demonstrated that loss of Ron in myeloid cells is sufficient to inhibit prostate cancer cell growth. Interestingly, depletion of CD8+ T-cells, but not CD4+ T-cells, was able to restore prostate tumor growth in hosts devoid of myeloid-specific Ron expression. These studies demonstrate a critical role for the Ron receptor in the tumor microenvironment, whereby Ron loss in tumor-associated macrophages inhibits prostate cancer cell growth, at least in part, by de-repressing the activity of CD8+ T cells.